Implementation of Language Politness Principles in Indonesian Language Learning Discussion Activities - Della Rency Melia Indah; Kasmantoni Kasmantoni; Bustomi Bustomi (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
This research is motivated by Indonesian Language Learning which requires students to master the six politeness principles. Namely the maxsim of wisdom, the maxsim of generosit, the maxsim of praise, the maxsim of humility, the maxsim of agreement, and the maxsim of sympathy. In class VIII A SMP Negeri 1 Kikim Tengah in discussion activities. The writing is the study exsamines how the implementation of politeness in Indonesian Language learning in class VIII teacher and students of SMP Negeri 1 Kikim Tengah, Lahat Regency during a discussion and what are the factors for violating the maxsims in the discussion. The type of this research is descriptive qualitative research. The subjects of this research are students of class VIII A SMP Negeri 1 Kikim Tengah, Lahat Regency, Meanwhile, the informants of this research are Indonesia Language Teacher at SMP Negeri 1 Kikim Tengah, Lahat Regency. The results of this study concluded that the implementation of politeness principles in student discussion activities, namely opening, explaining, question and answer, closing. The discussion process for students must be more thorough in mastering the principles of politeness in Indonesian language learning discussion activities, and the lecture method